Design and development of modular autonomous flying vehicle - Abedin, Jaber; Akmeliawati, Rini (UNSYS Digital, 2015)
In recent years, Vertical Take-off and Landing vehicles (VTOL) have gained popularity among researchers due to their capabilities of vertical stationary flight and maneuverability. As the consequences, many beneficial and unique applications of this type of vehicle can be found for both military and civilian purposes. Despite heightened interest in VTOL vehicles, research in this area until now has focused almost exclusively on rotorcraft platforms such as quadrotors. Very little research has been performed in extending the design of VTOL vehicles to a multi-rotor platform consisting of individual flight modules using distributed control. In this project, a multi-rotor platform consisting of modular flight vehicles using distributed control has been designed. The individual modules are able to communicate and coordinate with each other to fly in a variety of flight formations either as individual units flying in formation in a coordinated fashion or as larger units by physically combining and docking with each other. A distributed strategy for hover control based on the physical parameters of the distributed flight array (DFA) formed the basis of the flight control of the vehicles. The analysis of the prototype showed that the roll and the pitch angles achieved stabilization in the hovering state.